THE IMPACT OF MARITAL AND PARENTAL STATUS ON BURNOUT AND WELLBEING AMONG HOSPITALITY EMPLOYEES - Labus, Pero; Ostojić, Bojana; Lukić Nikolić, Jelena (The European Journal of Applied Economics, 2026)
This paper examines the relationship between marital and parental status and professional burnout among hospitality employees, utilizing the Maslach Burnout Inventory. Drawing on statistical evidence from a field study of 1,234 participants, the analysis reveals that marital and parental status significantly influence the three core dimensions of burnout. Marriage and parenthood appear to serve as protective resources, reducing emotional exhaustion and depersonalization, while simultaneously shaping different perceptions of personal accomplishment. Notably, the lower sense of accomplishment among married individuals suggests that competing with family and professional demands may constrain feelings of success, underscoring the dual role of family responsibilities as both supportive and demanding. These findings demonstrate that family-related factors are not merely demographic attributes but critical determinants of resilience and vulnerability in high-stress service industries such as hospitality. From a practical perspective, the results highlight the importance of family-supportive organizational policies, including flexible scheduling, parental leave, and wellness initiatives, to mitigate burnout and enhance employee wellbeing. Overall, this research advances understanding of how personal life circumstances intersect with professional burnout, offering insights that can guide organizational strategies, inform mental health interventions, and promote sustainable workforce practices aligned with global wellbeing and decent work agendas.
Keywords: burnout; wellbeing; marital status; parental status; employee retention; hospitality